The corporation and its employees: A case story - Dahl, Tor (Journal of business ethics, 1989)
One of the main objectives in the information society is to improve the quality of life. — Paying attention to the needs of people seems to be a key element in good ethical behaviour, says Tor Dahl, Managing Director of Manpower Scandinavia. In defining these needs, Manpower used Abraham Maslow's famous pyramid, his hierarchy of needs, as a model for trying to satisfy in practise the needs on each level., However, they went a step further, asking; what comes after Maslow? To mean something for others; togetherness and that people can be trusted and that they seek a purpose with their work, came out as answers. In his paper Mr. Dahl tells us how Manpower Scandinavia has developed a written set of values, which function as a basis for action and guidelines for behaviour, and where the key idea behind it all is to let people be self-managed. Furthermore, he shows us how Manpower has organised the company according to this conviction., — If your really have faith in people and show them trust, they will show you trust in return. Then you have a good basis for ethical behaviour, Tor Dahl concludes his paper.